2019
DOI: 10.1055/a-1007-8613
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper of the Task Force for Obstetrics and Prenatal Medicine (AGG – Section Preterm Birth) on the Placement, Removal and Surveillance of the Arabin Cervical Pessary in Patients at Risk for Spontaneous Preterm Birth

Abstract: This position paper describes clinically important, practical aspects of cervical pessary treatment. Transvaginal ultrasound is standard for the assessment of cervical length and selection of patients who may benefit from pessary treatment. Similar to other treatment modalities, the clinical use and placement of pessaries requires regular training. This training is essential for proper pessary placement in patients in emergency situations to prevent preterm delivery and optimize neonatal outcomes. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The fact that the majority of patients have reported positive changes in their lives during treatment may be in part related to the decreased concern about the risk of preterm birth. In addition, the presence of the pessary supporting the cervix may give relief of pressure sensations while walking or standing in some patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the majority of patients have reported positive changes in their lives during treatment may be in part related to the decreased concern about the risk of preterm birth. In addition, the presence of the pessary supporting the cervix may give relief of pressure sensations while walking or standing in some patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, the cervical pessary has been investigated in different settings in both singleton [ 12 17 ] and twin pregnancies [ 18 24 ]. It promotes an inclination of the uterocervical angle as visualized by MRI or clinically [ 25 , 26 ]. This mechanism is supposed to reduce the pressure on the lower uterine segment at the level of the internal cervical os and the cervix as studied in vivo by a change in maternal position [ 27 , 28 ], or in vitro by biomechanical engineering [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 After that presentation, the hospital included CP in the non-standard medication of our pharmacy and supported all of our cases and research with this device, based on just the economic aspect. Some information about cervical pessary has been already published for new users, [16][17][18] but many other aspects need to be pointed out about this subject.…”
Section: Opinion Open Accessmentioning
confidence: 99%
“…9 As part of the German task force to prevent preterm birth we have published guidelines about cervical pessary treatment based on approximately 1000 treated cases of the first author. 10 The complaints described by Norman et al 8 were never reported and may rather reflect lack of clinical expertise during insertion, continuity of care, reassurance, or removal and lack of audit. Biomechanical remodeling suggested that a relief of pressure to the lower uterine segment requires accurate positioning, i.e.…”
mentioning
confidence: 99%
“…In the STOPPIT‐2 trial, 8 the average treatment/center was three—leading to patient complaints as compared to centers with experience 9 . As part of the German task force to prevent preterm birth we have published guidelines about cervical pessary treatment based on approximately 1000 treated cases of the first author 10 . The complaints described by Norman et al 8 were never reported and may rather reflect lack of clinical expertise during insertion, continuity of care, reassurance, or removal and lack of audit.…”
mentioning
confidence: 99%